Dualwavelength fiber laser - Abdi, Mohamed Khalif (2021)
A Dual-wavelength erbium doped fiber laser (EDFL) is presented. The gain interest in recent decades due to their inherent characteristics such as narrow linewidth, high optical power. Generation of dual-wavelengths is realizable through Erbium Ytterbium Doped Fiber Amplifier (EYDFA) gain in the laser cavity. The lasing wavelength spacing is widely controlled in a range from 3 to 16.1 nm, which means the tunable can be achieved. The signal to noise ratio (OSNR) obtain as high as 60 dB. The fiber Bragg gratting FBG 1539.4 nm achieved and the output power of the EYDFA is fixed at 1 w. The Tunable BandPass Filter TBPF is put in the laser cavity. The laser FBG goes to port 1 then, TBPF will tune and passes to port 2. The FBG reflects only at the wavelength of 1539.4 nm and the rest passes through. The TBPF tuned from 1542.3 to 1555.5 nm. The TBPF is almost the same with FBG after thulium. The thulium function here is to stabilize and distribute energy from higher power to the low power. The minimum variation is 1.9 dB while the maximum is 2.87 dB. Hence, dual-wavelength fiber laser records the best performances with respect to the output power, the laser is found to be the most stable when applied enough power.